Omnidirectional Dual-Reflector Antenna with GO Shaped Main Reflector for Pattern Control in the Elevation Plane: OADC Case - José R. Bergmann; Fernando J. S. Moreira (International Journal of Antennas and Propagation)
This paper presents a formulation for shaping the main reflector of an axis-symmetric dual-reflector antenna designed to offer an omnidirectional coverage with an arbitrary radiation pattern in the vertical plane. The subreflector is generated by an axis-displaced conic, and the main reflector is shaped to achieve a prescribed far-field radiation pattern. The procedure is based on geometrical optics (GO) principles. Two distinct far-field ray structures are explored and their limitations are identified. The GO shaping results are validated by analysis provided by the accurate method of moments technique.